2012
DOI: 10.1136/vr.100199
|View full text |Cite
|
Sign up to set email alerts
|

Survey of travel‐related problems in dogs

Abstract: The aim of this study was to quantitatively assess the kind of transport dogs undergo, the behaviours displayed during transport, the prevalence of travel-related problems in dogs and owners' interventions to solve these problems. A convenience sample of 907 dog owners completed a questionnaire containing 16 multiple-choice questions. All dogs had been transported by car at least once, but 4.7 per cent were no longer transported. 76.2 per cent of animals always responded positively to car transport, the rest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Results of a questionnaire study among dog owners suggest that dogs used to travelling by car since puppy age were less likely to respond negatively to road transport than dogs transported as adults only. According to their owners’ perception, however, 24% out of close to 1000 dogs experienced problems when transported by car [ 22 ]. This suggests that although a certain degree of adaptation occurs in most dogs over longer times, transport is still perceived as stressful or negative by a substantial percentage of dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a questionnaire study among dog owners suggest that dogs used to travelling by car since puppy age were less likely to respond negatively to road transport than dogs transported as adults only. According to their owners’ perception, however, 24% out of close to 1000 dogs experienced problems when transported by car [ 22 ]. This suggests that although a certain degree of adaptation occurs in most dogs over longer times, transport is still perceived as stressful or negative by a substantial percentage of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey among dog owners, 24% of dogs were reported to have problems when travelling by car. When dogs had become used to travelling by car as puppies, the likelihood of transport-related problems at adult age was reduced, suggesting a certain degree of habituation [ 22 ]. In two experimental studies, road transport of dogs was associated with increases in heart rate, behavioral changes and an increase in the neutrophil to leukocyte ratio [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of the transporters, who often operated independently from the larger organizations represented in our study, would provide insight into efforts made to minimize the potential negative impacts of transport on dog welfare and would draw attention to transport-related welfare concerns that merit consideration. Welfare issues associated with long-distance transfer are an area of particular concern given that transport can adversely affect dog behavior and has the potential to create new behavior problems (e.g., phobias) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detecting the response to a stressor is important, but assessing the time of recovery is even more important for its impact on dog welfare: some poor welfare states may be acceptable if they are short or if the animal can tolerate them (Morton 2007); whereas a prolonged stress can be highly detrimental. Poor welfare in the waiting room is particularly important if the dog has to visit the veterinary clinic regularly, if it leads to travelrelated problems (Mariti et al 2012a), or if dogs (as reported by many owners) anticipate going to the vet, because they might develop anxiety (Overall 2014).…”
Section: Discussionmentioning
confidence: 99%